sinx×2sinx-tanx×sin2x
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 00:46:42
sinx×2sinx-tanx×sin2xsinx×2sinx-tanx×sin2xsinx×2sinx-tanx×sin2xsinx×2sinx-tanx×sin2x=2sinx*sinx-tanx
sinx×2sinx-tanx×sin2x
sinx×2sinx-tanx×sin2x
sinx×2sinx-tanx×sin2x
sinx×2sinx-tanx×sin2x
=2sinx*sinx-tanx*2sinx*cosx
=2sinx*sinx-2sinx*sinx=0
解sinx×2sinx-tanx×sin2x
=2sin^2x-(sinx/cosx)×2sinxcosx
=2sin^2x-(sinx)×2sinx
=2sin^2x-2(sinx)sinx
=2sin^2x-2sin^2x
=0
sinx×2sinx-tanx×sin2x
证明:tanx sinx / (tanx -sinx)=(tanx+sinx) / tanx sinx
证明:(sinX*tanX)/(tanX-sinX)=(tanX+sinX)/(tanX*sinX)
tanX-sinX
化简:(sinx)^2/(sinx-cosx)-(sinx+cosx)/((tanx)^2-1)
证明tanx^2-sinx^2=tanx^2 * sinx^2
化简sinx(1+tanx*tanx/2)
(-cosx-sinx+2)/(tanx+cotx)
已知tanx=2,求(sinx*sinx+sinx*cosx)/(sinx*sinx+1)
lim(tanx-sinx)/(sinx)3
tanx.sinx/tanx-sinx=tanx+sinx/tanxsinx证相等
1-2sinx*cosx/(cosx+sinx)(cosx-sinx)=1-tanx/(1+tanx)怎么证明
已知tanx=2,计算(1)、2cosx-3sinx/sinx+cosx.(2)、sinx+cosx-sinx
求证:(1+sinx+cosx)/(1+sinx-cosx)-(1+sinx-cosx)/(1+sinx+cosx)=2/tanx
已知cosx-sinx=√2sinx,求证(cosx-sinx)/(cosx+sinx)=tanx
cosx-sinx=根号2sinx,求证tanx=cosx-sinx/cosx+sinx谢谢了,
y=sinx/|sinx |+|cosx|/cosx +tanx/|tanx| +cotx/|cotx|1.函数y=sinx/|sinx |+|cosx|/cosx +tanx/|tanx| +|cotx|/cotx的值域是2.若sin2α>0,且cosα
tanx=2,则sinx+cosx/2sinx-cosx嗯